Factors Influencing Segari E-Grocery’s Purchase Intention Moderated by Gender and Age - Vashti Velda Verianto; Yosef Budi Susanto; Daniel Susilo (Profesional Muda Cendekia Publishing, 2023)
Mobility restriction during the Covid-19 pandemic is one of many living aspects that changed people’s behaviour. The emergence of e-groceries helps many people get their groceries with the restrictions given. Segari is one of the e-grocery that emerged during the pandemic. In order to increase its sales and revenue and to be able to keep its growth even post-pandemic, Segari needs to understand its consumer’s behaviour better, so this research was conducted. We used the modified version of UTAUT (Unified Theory of Acceptance and Use) as the research model. We examined the effect of brand association, perceived ease of use, perceived usefulness, perceived security, and perceived price towards Segari’s purchase intention. We also examine the moderating effect of gender and age in this research. Quantitative research was done using SEM-PLS and PLS-MGA for the moderating effect. Findings show that brand association, perceived usefulness, and perceived security significantly affect Segari’s purchase intention, while perceived ease of use and perceived price do not significantly affect Segari’s purchase intention. Gender differs in the effect of brand association and perceived security and does not differ in the effect of perceived ease of use, perceived price, and perceived usefulness. Age differs in the effect of perceived security on Segari’s purchase intention and not in the effect of brand association, perceived ease of use, perceived usefulness, and perceived price on Segari’s purchase intention.